Microbial Profiles of Patients With Antipsychotic-Related Constipation Treated With Electroacupuncture - Zheng, Yuanjia; Jiang, Xiumin; Gao, Yacen; Yuan, Lexin; Wang, Xiaotong; Wu, Shengwei; Xia, Yucen; Yao, Lin; Yan, Jinglan; Liu, Lanying; Wei, Yingdong; Song, Zhiqiang; et al. (Frontiers in Medicine, 2021)
Antipsychotic-related constipation (APRC) is one of the most common side effects of taking antipsychotic medication. APRC can seriously impact patient quality of life and is potentially fatal, though the efficacy of current APRC treatments is low for most patients. In this study, we conducted a controlled, pilot randomized, sham-electroacupuncture (SEA) study to assess the efficacy of electroacupuncture (EA) in patients with APRC. We used 16S rRNA gene sequencing to assess the microbial profiles of these patients and analyze how EA treatments affected their bacteria. Methods: We treated 133 APRC patients with randomly assigned EA treatments or SEA treatments for 4 consecutive weeks, fully evaluating the patients 8 weeks after treatment. The participants, outcome assessors, and statistics were all blind to the EA and SEA treatments. Outcomes assessed included changes in spontaneous bowel movements (SBMs) and the frequency of rescue measures. We detected assessed the microbial diversity of stool specimens both before and after EA treatment using 16S rRNA gene sequencing. Results: Both EA and SEA treatments reduced the need for constipation rescue measures and did not have serious side effects. EA treatments were better than SEA treatments at increasing SBMs and reducing rescue measures. The diversity of gut microbiota changed after EA treatment. LEfSe analysis indicated changes in the genus (belonging to phylum Proteobacteria) of gut microbiota in patients following EA treatment. Conclusions: This study found that EA treatment is effective and safe for patients with APRC, and could be associated with changes in their microbial profiles. Further study, with larger sample sizes, is needed to explore the efficacy of EA intervention as a clinical treatment for APRC. Trial Registration: ChiCTR, ChiCTR-ONC-17010842, http://www.chictr.org.cn/showproj.aspx?proj=18420.